Sitting together: How to analyse technical data with a gender perspective - Ouma, Emily A. (International Livestock Research Institute, 2016)
Interview with Emily Ouma (ILRI) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684